REGRESSION EQUATIONS FOR STATURE ESTIMATION AMONG MEDICAL STUDENTS OF GHAZIABAD - Rakhee Verma; Syed Esam Mahmood (Medsci Publications, 2015)
Introduction: Ossification and maturation in the foot occurs earlier than the long bones and therefore, during adolescence height could be more accurately predicted from foot measurement as compared to that from long bones. This study was undertaken to find out the cor- relation between foot length and height of an individual and to de- rive regression formulae to estimate the height from the foot length in the study population. Materials & Method: This cross sectional study was conducted at Ghaziabad among 150 healthy medical students aged between be- tween 17 - 25 years. Foot length and height was measured. Statistical analysis was performed using SPSS software. Karl Pearson's correla- tion coefficient and Linear Regression analysis was applied. Results: The mean height and mean foot length was 164.44 cm and 24.65 cm respectively. A strong positive correlation between height and foot length of individuals was found. The regression equation for height and foot length was found to be Y(height) = 4.399 X(mean foot length) + 55.988. Conclusion: Foot length is a useful parameter in stature estimation. Further detailed study for stature estimation using other parameters like hand and toe length should be conducted to establish regression equations.